2002
DOI: 10.1088/0268-1242/18/2/308
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence and structural properties of cadmium sulphide thin films grown by different techniques

Abstract: In this paper, we present a comparative study of photoluminescence and its relation to the structural properties of cadmium sulphide (CdS) thin films grown by chemical bath deposition (CBD), close spaced vapour transport, laser ablation (LA) and sputtering. Taking into account that the physical properties of CdS thin films depend upon the growth technique and the optimization of the deposition conditions for each technique, we show that the best crystal perfection occurs for LA-CdS films since the main photolu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(32 citation statements)
references
References 16 publications
(16 reference statements)
2
30
0
Order By: Relevance
“…[41][42][43][44][45][46] Depending on the growth method and CdS grain size the red luminescence is found centered at 1.67, 44 43,46 It is believed that the red luminescence is caused by transitions of electrons trapped in surface states to the valence band, 39,40 and this effect is therefore correlated with the accumulation of crystallographic defects in CdS layers grown at low deposition temperatures. Annealing of smallgrained CdS films increases grain size, decreases the number of grain boundaries, heals lattice defects, and reduces strain in the layer.…”
Section: -5mentioning
confidence: 99%
See 2 more Smart Citations
“…[41][42][43][44][45][46] Depending on the growth method and CdS grain size the red luminescence is found centered at 1.67, 44 43,46 It is believed that the red luminescence is caused by transitions of electrons trapped in surface states to the valence band, 39,40 and this effect is therefore correlated with the accumulation of crystallographic defects in CdS layers grown at low deposition temperatures. Annealing of smallgrained CdS films increases grain size, decreases the number of grain boundaries, heals lattice defects, and reduces strain in the layer.…”
Section: -5mentioning
confidence: 99%
“…In general, the red emission band is associated with the involvement of sulfur vacancies in radiative recombination. 41,44 Vigil et al 46 describe luminescence observed at 1.83 eV with transitions from V S 2+ states to the valence band. CdCl 2 has a significant effect on recrystallization of CBD-CdS grains and acts as a fluxing agent at low temperatures; we thus expected to see a reduction in the red luminescence with CdCl 2 treatment.…”
Section: -5mentioning
confidence: 99%
See 1 more Smart Citation
“…All the films shows an intense peaks at 495 nm (2.51 eV), 520 nm (2.4 eV) and at 595 nm (2.09 eV) respectively. PL band appearing in the range of 2.18-2.54 eV are called green bands; band appearing between 2.07 -2.18 eV are typically referred to as yellow bands; the orange band is located between 2 -2.07 eV, and luminescence observed around 1.54 -2 eV is called the infrared / red band [16]. A donor level of 0.21 eV below the conduction band is suggested to be related to a cadmium interstitial Cd or to a sulfur vacancy VS.…”
Section: A Photoluminescence Analysismentioning
confidence: 99%
“…However, given that CdS sublimes quite freely at 800 C, even in 100 mtorr of argon, [3] any increase in NP size seems unlikely. Sublimation of the CdS NPs from the silicon surface at 800 C would seem to be confirmed by the authors' own in-situ X-ray photoelectron spectroscopy (XPS) data (see Fig.…”
mentioning
confidence: 99%